In Healthy Young Men, a Short Exhaustive Exercise Alters the Oxidative Stress Only Slightly, Independent of the Actual Fitness. (17th February 2016) - Finkler, Maya; Hochman, Ayala; Pinchuk, Ilya; Lichtenberg, Dov
Abstract : The aim of the present study was to evaluate the apparent disagreement regarding the effect of a typical cycling progressive exercise, commonly used to assessV O 2 m a x, on the kinetics of ex vivo copper induced peroxidation of serum lipids. Thirty-two (32) healthy young men, aged 24–30 years, who do not smoke and do not take any food supplements, participated in the study. Blood was withdrawn from each participant at three time points (before the exercise and 5 minutes and one hour after exercise). Copper induced peroxidation of sera made of the blood samples was monitored by spectrophotometry. For comparison, we also assayed TBARS concentration and the activity of oxidation-related enzymes. The physical exercise resulted in a slight and reversible increase of TBARS and slight changes in the activities of the studied antioxidant enzymes and the lag preceding peroxidation did not change substantially. Most altered parameters returned to baseline level one hour after exercise. Notably, the exercise-induced changes in OS did not correlate with the physical fitness of the subjects, as evaluated in this study (V O 2 m a x = 30–60 mL/min/kg). We conclude that in healthy young fit men a short exhaustive exercise alters only slightly the OS, independent of the actual physical fitness.